Caffeine and Caffeic Acid as Acetylcholinesterase Inhibitors: In Silico Perspectives - Stephanus Satria Wira Waskitha; Bonifacius Ivan Wiranata; Julyus Jason Mark; Herluin Sekar Krisantia; Natalia Kristina; Glory Ivana Ardine; Chrisologus Ivan Prasetyo; Michael Raharja Gani; Florentinus Dika Octa Riswanto; Enade Perdana Istyastono (Sanata Dharma University, 2025)
Alzheimer's disease (AD) has been recognized as a significant issue affecting population health globally and tended to increase over the years. The utilization of natural products for AD treatments has been widely studied, which possibly offers better outcomes with minimum side effects. Coffee consumption has been subjected as a lifestyle propensity, which offers beneficial advantages including reducing the risk of AD. Bioactive natural compounds contained in coffee such as caffeine and caffeic acid have been experimentally proven to be acetylcholinesterase (AChE) inhibitors, a pivotal target enzyme for AD treatments. This research aimed to explore the dynamics interactions of caffeine and caffeic acid in the AChE active site using the in silico approach. In this study, 100 redocking and docking simulations were implemented before the molecular dynamics (MD) simulations. The 55-ns MD simulations of huprine X, caffeine, and caffeic acid were implemented to study the dynamics interactions. Conformational stability, free energies of binding, and interaction hotspots were identified during the simulations. Our findings informed that caffeine interacted in the active site during the simulations, revealing the importance of the imidazole ring in maintaining the interactions. In contrast, caffeic acid interacted longer in the plausible allosteric site, forming ionic, hydrogen bonds, and aromatic interactions.